Effects of culture on online engagement: The University of the Philippines Open University (UPOU) setting - Librero, Al Francis D. (International Journal on Open and Distance e-Learning, 2020)
This study covers the experience of the author with a team of learners from the University of the Philippines Open University’s (UPOU’s) Bachelor of Arts in Multimedia Studies (BAMS) program. The goal of the team was to practice student co-creation of multimedia content, with the hopes of building an online community to support the project, as well as the participants of the project themselves. The project did not succeed, as far as production was concerned, stemming from a failure to foster the level of interaction and engagement necessary to facilitate co-creation, as well as the development of a community. Through interviews with the project members, it was found out that cultural influences were surrounding the lack of success, such as fear of embarrassment and an inherent need for a more established hierarchy. The technology employed did not exacerbate the situation, but it is in a position to be of more help in fostering a higher level of interaction.